2018
DOI: 10.3389/fimmu.2018.01345
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma Stem-Like Cells Are More Susceptible Than Differentiated Cells to Natural Killer Cell Lysis Mediated Through Killer Immunoglobulin-Like Receptors–Human Leukocyte Antigen Ligand Mismatch and Activation Receptor–Ligand Interactions

Abstract: Glioblastoma (GBM) is the most aggressive brain malignancy in adults, where survival is approximately 14.6 months. Novel therapies are urgently needed and immunotherapy has hailed a new dawn for treatment of solid tumors. Natural killer (NK) cells may be amenable therapeutic effectors against heterogeneous GBM, since they also do not require co-stimulation and antigen specificity. However, it is unclear how culture media routinely used in pre-clinical studies affect GBM cell responses to NK-mediated cytotoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 69 publications
0
36
0
Order By: Relevance
“…NK cells have been shown to specifically target glioblastoma stem cells 38 and can circumvent antigen loss seen with CAR-T-based modalities 39 . A clinical trial of NK cell infusion for pediatric patients with CNS tumors is already in-progress 40 and preliminary results indicate an excellent safety profile.…”
Section: Discussionmentioning
confidence: 99%
“…NK cells have been shown to specifically target glioblastoma stem cells 38 and can circumvent antigen loss seen with CAR-T-based modalities 39 . A clinical trial of NK cell infusion for pediatric patients with CNS tumors is already in-progress 40 and preliminary results indicate an excellent safety profile.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results using NK cell therapy in animal models of solid tumors or in clinical trials are disappointing, even if NK cells can eliminate the engrafted cell type or the primary tumor cells in vitro (11)(12)(13). In this context, it should be noted that different culture media affect tumor recognition by NK cells (40). In summary, there is not any expansion protocol that produces allogeneic NK cells able to efficiently eliminate solid tumor cells in vivo.…”
Section: Mechanisms Of Nk Cell Expansionmentioning
confidence: 99%
“…Why NK cells destroy most targets in vitro but not in vivo is unknown. Tumor cells strongly modify the expression of ligands, which are recognized by NK cell activating or inhibiting receptors when cultured in vitro (40). This could lead to the mistrust that those specific tumor cells would be NK sensitive or resistant in vivo.…”
Section: Mechanisms Of Nk Cell Expansionmentioning
confidence: 99%
“…Studies have shown that CAR-engineered and PD-1 inhibited NK cells exhibit antitumor effects and can induce apoptosis of GB cells [273][274][275][276]. GB stem-like cells are more susceptible to lysis by NK cells than differentiated GB cells [277]. In animal models, pretreatment of GB with bortezomib has been shown to promote NK cell cytotoxicity and to inhibit tumor growth ultimately leading to prolonged survival [278].…”
Section: Nk Cells In Solid Tumorsmentioning
confidence: 99%